Conservative management for retained products of conception after less than 22 weeks of gestation. Issue 10 (5th August 2020) - Shitanaka, Shimpei; Chigusa, Yoshitsugu; Kawahara, Shunsuke; Kawasaki, Kaoru; Mogami, Haruta; Mandai, Masaki; Kondoh, Eiji
Abstract: Aim: The aim of the study was to investigate the efficacy of conservative treatment in cases of retained products of conception (RPOC) with a preceding pregnancy of less than 22 weeks and to assess whether serum beta‐human chorionic gonadotropin (hCG) levels could be a useful index to monitor the progress of treatment. Methods: This is a case series of patients with RPOC developed after less than 22 weeks of gestation and managed expectantly with serial serum hCG measurement between 2011 and 2017. The clinical data of subjects were reviewed retrospectively. Cases that did not require invasive treatment such as surgery were designated as conservative management success. Results: A total of 19 cases were eligible: 14 miscarriages and 5 induced abortions. Eleven patients underwent dilatation and curettage. The diagnosis of RPOC was made 35 (8–80) days after abortion. All patients were successfully treated with conservative management. Serum hCG levels at diagnosis were 29.6 (3.2–1585) mIU/mL. Serial measurement of serum hCG was continued until the levels became lower than the cutoff value, and the mean duration to hCG disappearance was 67.5 (6–183) days. In all cases, RPOC vanished spontaneously 77 (27–184) days after diagnosis. The disappearance of RPOC in the uterine cavity was subsequent to a significant decrease in serum hCG. Once serum hCG levels reached the cutoff value, no bleeding episodes were observed. Conclusion: Conservative management for RPOC might be acceptable and effective. Furthermore, serial serum hCG levels reflect the activity of RPOC, and hCG may be a reliable index to monitor the progress of treatment.